Educazione all’uguaglianza di genere ed educazione linguistica (Strumenti per la didattica e la ricerca, 2024)
The book explores the debate on gender equality in the language that emerged since the end of the 1980s, when Alma Sabatini highlighted the androcentric character of Italian in the linguistic choices of speakers. Today, as then, to ensure equal visibility for genders, it is a matter of respecting the ‘normal’ grammatical rules of language. The volume collects reflections of linguists inviting to develop in training contexts a greater sensitivity to the principle of equality between the genders, presenting examples of good and bad practices in public communication, pedagogic and didactic. The aim of this book is to highlight the importance of forging a deal within the community of speakers in order to affirm the equal dignity of the genders through language choices.